The Association Between Habitual Sleep Duration and Blood Pressure Control in United States (US) Adults with Hypertension [Letter] - Lameky VY; Tasijawa O (Dove Medical Press, 2024)
Vernando Yanry Lameky,1 Oci Tasijawa2 1Department of Nursing, Universitas Kristen Indonesia Maluku, Ambon, Maluku, Indonesia; 2Book Publisher, Ghema Berkat Abadi, Ambon, Maluku, IndonesiaCorrespondence: Vernando Yanry Lameky, Department of Nursing, Universitas Kristen Indonesia Maluku, Jl. Ot pattimaipauw, Ambon, Maluku, Indonesia, Email vernandoyanrylameky@gmail.com